A Collective Household Model of Time Allocation - A Comparison of Native Dutch and Immigrant Households in The Netherlands - Chris van Klaveren; Bernard M.S. van Praag; Henriette Maassen van den Brink (Tinbergen Institute, 2006)
Although the number of immigrant households in the Netherlands is substantial, the labor supply choices of this group are usually neglected in empirical studies because these households are usually under-sampled. We use a stratified sample of Turkish, Surinamese/Antillean and Dutch households that enables us to discuss how two-earner households allocate their time to different activities. In order to do so, we empirically estimate a collective household labor supply model. The main findings are that: (1) Leisure and household income are the most important variables in the utility function of the male; (2) Leisure, total household production and total household production interacted with family size are important variables in the utility function of the female. The latter two are especially important for Turkish and Surinamese/Antillean females; (3) The utility of Turkish and Dutch males weighs slightly more than the utility of the partner in the household utility f! unction. For Surinamese/Antillean families we find the opposite; (4) Utility weighting depends on the presence of children and on the hourly wage rates of both partners; (5) The labor supply curve is forward bending for both male and female in terms of their own wage. The labor supply curve is backward bending for both male and female in terms of the partners wage. We find this for all household types; (7) The presence of(more) children reduces the hours of labor supplied by women and increases the number of hours supplied by men.
Keywords: D12; D13; J22; 330; Collective household models; Labor supply; Intra-household; time allocation